Towards a Theological Overcoming of Anthropocentrism. The Vegetarian Choice - Trianni, Paolo (Wydział Filozoficzny UAM, 2020)
The article intends to demonstrate that a theology of vegetarianism is possible, despite some contrary evidence present in the biblical texts. Like other theologies dealing with issues not directly voiced in the Bible, it becomes possible to interpret the biblical statements in a new way, on the bases of a specific methodology. As a result, an objective comprehension will go back inductively to Sacred Scripture. The article advocates for applying this new method as well as for introducing its ethical implications into the Christian tradition. An additional supportive argument in favour of establishing the new understanding can be found in the history of the Roman Church, besides the consolidated custom of carnivorous nutrition: there has been no shortage of positions in favour of vegetarian asceticism. This stance was also represented by Thomas Aquinas. By valorizing classic Christian authors in favour of vegetarianism (starting with Jerome), the inauguration of the theology of vegetarianism becomes legitimised. Such an inauguration would reorient Christian thought toward reconsidering cosmology, ecology and topical contemporary issues such as anthropocentrism and speciesism.
Keywords: theology of vegetarianism; Christian vegetarianism; gnosticism; theology of animals; anthropocentrism; Christian-Jewish carnivorous custom